Guy Debord and Structuralism: toward a critique of the university “Rank-and-file” - Galhardo, Davi (Sofia, 2026)
Nearly three decades after the first Brazilian edition of La société du spectacle (1967) was published in 1997 – translated by Estela dos Santos Abreu (1932-) and due to the efforts of the publisher Contraponto from Rio de Janeiro, founded by César de Queiroz Benjamin (1954-) – it is fair to say that the “theory book” of the Situationist International (1957-1972) has had a significant impact on the Brazilian public sphere. Since then, the French critical theorist has increasingly penetrated the political and academic imagination of our country, inspiring political-cultural actions and publications addressing various aspects of his work. At present, however, I would like to emphasize that there remains a facet of this work that is still lacking in more robust discussion among our peers: namely, Debord’s critique of French Structuralism. To pursue this objective, I will examine a few selected paragraphs from the 1967 book and three letters concerning Louis Althusser (1918-1990) that appear in Debord’s correspondence. This material will be confronted with brief but crucial passages from works by prominent figures of French Structuralism in the 1950s and 1960s, notably Roland Barthes (1915-1980) and Althusser himself. This philosophical reflection is guided by a key interpretative thread: the mistranslation in the Brazilian edition that rendered Structuralism as the “university thought of the lower clergy” rather than the “university thought of the middle ranks.” The original theoretical contribution and hypothesis of this interpretative essay, therefore, aims to demonstrate the fruitfulness of Debord’s methodological approach to ‘détournement’ as a key to understanding contemporary history, considering that Brazilian intellectual circles are still deeply marked by Structuralist influence. Broadly speaking, Debord emphasized that, from another point of view, errors and failures can be transformed into victories. Indeed, this procedure could be expanded in future historical struggles and, perhaps, in the transformation of social life as we know it now.
Keywords: society of spectacle; situationist international; French structuralism; Détournement; critical theory